Comparison of Nestin‐Expressing Multipotent Stem Cells in the Tongue Fungiform Papilla and Vibrissa Hair Follicle. Issue 6 (June 2014) - Mii, Sumiyuki; Amoh, Yasuyuki; Katsuoka, Kensei; Hoffman, Robert M.
ABSTRACT We have previously reported that hair follicles contain multipotent stem cells, which express nestin and participate in follicle growth at anagen as well as in the extension of the follicle sensory nerve. The nestin‐driven green fluorescent protein (ND‐GFP) transgenic mouse labels all nestin‐expressing cells with GFP. The hair follicle nestin‐GFP cells can differentiate into neurons, Schwann cells, and other cell types. In this study, we describe nestin‐expressing multipotent stem cells in the fungiform papilla in the tongue. The nestin‐expressing multipotent stem cells in the fungiform papilla are located around a peripheral sensory nerve immediately below the taste bud and co‐express the neural crest cell marker p75NTR. The fungiform papilla cells formed spheres in suspension culture in DMEM‐F12 medium supplemented with basic fibroblast growth factor (bFGF). The spheres consisted of nestin‐expressing cells that co‐expressed the neural crest marker p75NTR and which developed expression of the stem cell marker CD34. P75NTR, CD34 and nestin co‐expression suggested that nestin‐expressing cells comprising the fungiform papilla spheres were in a relatively undifferentiated state. The nestin‐expressing cells of these spheres acquired the following markers: β III tubulin typical of nerve cells; GFAP typical of glial cells; K15 typical of keratinocytes; and smooth‐muscle antigen (SMA), after transfer to RPMI 1640 medium with 10% fetal bovine serum (FBS), suggesting they differentiated into multiple cell types. The results of the current study indicate nestin‐expressing fungiform papilla cells and the nestin‐expressing hair follicle stem cells have common features of cell morphology and ability to differentiate into multiple cell types, suggesting their remarkable similarity. J. Cell. Biochem. 115: 1070–1076, 2014. © 2013 Wiley Periodicals, Inc.